2008
DOI: 10.1029/2007gl032291
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires dynamic in the larch dominance zone

Abstract: A fire return intervals (FRI) for zone of larch dominance and “larch‐mixed taiga” ecotone was studied. Extreme fire events were connected with summer air temperature deviations. Average FRI determined from stem fire scar dating was 82 ± 7 years for the zone of larch dominance, and 77 ± 20 for the “larch‐mixed taiga” ecotone. For the zone of larch dominance FRI on north‐east facing slopes was 86 ± 11 years, for south‐west facing slopes at 61 ± 8 years, for flat terrain at 68 ± 14 years, and for bogs 139 ± 17 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 13 publications
(17 reference statements)
6
41
1
Order By: Relevance
“…Furthermore, they are similar to dendrochronological estimates of fire return interval along the forest-tundra ecotone in central Siberia (130-350 yr, mean = 200 ± 50 yr) (Kharuk et al, 2011). Our fire rotation estimate for the mountain larch forests (64.5-67 • N) was slightly greater than the fire return interval determined for larch-dominated communities (∼ 64 • N) in central Siberia (Kharuk et al, 2008(Kharuk et al, , 2011, potentially due to slightly cooler temperatures and less human disturbance of the landscape. Mean annual fire density has been estimated to be 2.0 fires per 10 4 km 2 for Siberian mountain-tundra open forests (Valendik, 1996;Furyaev et al, 2001), though in our study area annual fire density between 2000-2007 averaged 0.3 ± 0.3 fires per 10 4 km 2 along the forest-tundra ecotone and 1.0 ± 1.0 fires per 10 4 km 2 in the Kolyma Mountains.…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern supporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, they are similar to dendrochronological estimates of fire return interval along the forest-tundra ecotone in central Siberia (130-350 yr, mean = 200 ± 50 yr) (Kharuk et al, 2011). Our fire rotation estimate for the mountain larch forests (64.5-67 • N) was slightly greater than the fire return interval determined for larch-dominated communities (∼ 64 • N) in central Siberia (Kharuk et al, 2008(Kharuk et al, , 2011, potentially due to slightly cooler temperatures and less human disturbance of the landscape. Mean annual fire density has been estimated to be 2.0 fires per 10 4 km 2 for Siberian mountain-tundra open forests (Valendik, 1996;Furyaev et al, 2001), though in our study area annual fire density between 2000-2007 averaged 0.3 ± 0.3 fires per 10 4 km 2 along the forest-tundra ecotone and 1.0 ± 1.0 fires per 10 4 km 2 in the Kolyma Mountains.…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern supporting
confidence: 62%
“…Eurasia experienced a record-breaking heat wave in (IPCC, 2007 that was associated with an extreme fire season across Siberia (Soja et al, 2007). Extreme fire events in the larch-dominated forests of central Siberia have previously been linked with summer air temperature deviations (Kharuk et al, 2008). During the positive phase of the AO, high pressures at northern mid-latitudes enhance the drying of phytomass and lead to a positive association between annual burned area and summer temperatures in central Siberia (Balzter et al, 2005).…”
Section: Fire Regime Along the Forest-tundra Ecotone In Northeastern mentioning
confidence: 99%
“…For example, the date of the first fire varied by up to 30 days. The fire return interval (we obtained earlier [6,20,21]) increased along the latitudinal gradient (Figure 6b). It varied from 80 years at 64° N to about 200 years at the latitude of the Arctic Circle.…”
Section: Fire Danger Period and Fire Return Intervalsmentioning
confidence: 95%
“…Trees were sampled until at least 12 samples were collected. In this study we used earlier obtained data on FRI in northern larch forests [6,20,21] which were analyzed against insolation along the meridian. Test sites where FRI data were obtained are shown on Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In Siberian larch forest, the fire regimes can be highly localized, contingent on soil moisture, permafrost status, and understory vegetation characteristics. For example, both satellite and dendrochronological data have shown that fire return interval is generally longer in northern regions (Kharuk et al 2011) and northeast-facing slopes (Kharuk et al 2008). Therefore, higher solar radiation and more frequent fire could promote the permafrost thaw and drainage on southwest-facing slopes.…”
Section: Comparison With Other Studies On Larch Forestsmentioning
confidence: 99%